Hepatoprotective Natural Products - Omayma A. Eldahshan (Ain Shams University, 2017)
Egypt holds a unique position in the epidemiology of liver diseases and cancer. We, here, shed the light on some important plant extracts and pure compounds that could be used as a new building unit for treatment of liver diseases.